The Effect of Aloe Vera Gel on Symptomatic Treatment of Pruritus Gravidarum - Meti Widiya Lestari; Nita Nurvita; Salma Thufailah; Ai Lela Nurul Muhlis Khoeriah (Jurnal Bidan Cerdas, 2025)
Background: Pruritus is a common discomfort occurring in the second and third trimesters of pregnancy, triggering a scratch. The treatment of pruritus can be administered through pharmacological and non-pharmacological therapies; however, many pregnant women avoid pharmacological medications due to concerns regarding potential adverse effects on the fetus. Topical Aloe vera gel is a recommended non-pharmacological alternative with no side effects for mother or infant. This research investigates the impact of Aloe vera gel application on pruritus in pregnant women. Method: This research used a one-group pretest-posttest design. 15 third-trimester pregnant women with pruritus were selected by purposive sampling at Mangkubumi Health Center. Participants applied the treatment twice daily for two weeks. Result: Before the aloe vera gel intervention, 40% of participants experienced mild itching and 60% moderate itching. Post-intervention, 6.6% reported complete relief, while 93.4% showed decreased itching intensity. Based on the Wilcoxon statistical test, a highly significant difference was observed (p = 0,001). Conclusion: It can be concluded that there was a statistically significant effect of aloe vera gel for reducing pruritus in pregnant women.